(untitled) (Argos, 2025)
This paper studies the Catalogue of Ships of the Iliad and the Homeric Hymns to Dionysus, Demeter and Apolo as part of the genre of travel literature (periplous). Also it considers space as a social project in which political and religious ideas are expressed. It argues that the geography represented in the Catalogue and the Hymns takes part in the construction of Greek identity and panhellenic ideas.